Prenatal Development of Compartment 1 of the Stomach in the One-Humped Camel (Camelus dromedarius): Topography and Gross Anatomy - Ibrahim, Mohammed I. A.; Siddig, Rasha S. A. (Journal of Veterinary Medicine and Animal Production, 2021)
Gross anatomical and biometric study was conducted on compartment 1 of the stomach of 18 fetuses of the one-humped camel (Camelus dromedarius). The approximate age of the fetuses was estimated according to the curved crown vertebral rump length (CVRL) and accordingly, they were classified into first trimester (71 to 131 days old foetus), second trimester (134 to 243 days old foetus) and third trimester (245 to 393 days old foetus). During Morphogenesis, the stomach was differentiated into four compartments (1, 2, 3, and 4) at 89 days old foetus. During the three trimesters, compartment 1 formed the largest part of the stomach. During the first trimester, compartment 1 was smooth, oval in shape, and composed of two sacs; cranial and caudal. In fetuses from 119 days of age and up to the time of delivery, compartment 1 was round in shape, and separated by an oblique transverse groove into two sacs: small cranioventral and large caudodorsal. The cranioventral sac extended ventrally and covers compartment 2. The caudodorsal sac presented a glandular region ventrally which is sacculated externally and in relation to the small intestine. During the second and third trimesters, compartment 1 was gradually increased in size, and extended from the 8th rib to the 4th lumbar vertebra. The cranioventral sac presented ventrally two blind sacs. Biometrical results showed that during prenatal development, the average body weight, stomach weight, and the diameter of compartment 1, were strongly correlated with the CVRL